2012
DOI: 10.1155/2012/604204
|View full text |Cite
|
Sign up to set email alerts
|

Successfully Improving Ocular Drug Delivery Using the Cationic Nanoemulsion, Novasorb

Abstract: Topical ophthalmic delivery of active ingredients can be achieved using cationic nanoemulsions. In the last decade, Novagali Pharma has successfully developed and marketed Novasorb, an advanced pharmaceutical technology for the treatment of ophthalmic diseases. This paper describes the main steps in the development of cationic nanoemulsions from formulation to evaluation in clinical trials. A major challenge of the formulation work was the selection of a cationic agent with an acceptable safety profile that wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
229
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(248 citation statements)
references
References 49 publications
4
229
0
15
Order By: Relevance
“…This is a smart strategy that combines the positive surface charge of the particles and the negative surface charge of ocular mucosa by means of an electrostatic attraction. This approach could increase the drugs retention time in the eye as well as improve nanoparticles bioadhesion (Lallemand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is a smart strategy that combines the positive surface charge of the particles and the negative surface charge of ocular mucosa by means of an electrostatic attraction. This approach could increase the drugs retention time in the eye as well as improve nanoparticles bioadhesion (Lallemand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some literatures have reported that cationic nanoemulsions can not only improve the permeability of poor water-soluble drugs 25 but also form complexes with macromolecular drugs (containing functional groups with a large number of negatively charge), such as nucleic acids, proteins, and other large molecules, to protect them from enzyme degradation and improve their absorption. 26 The absorption mechanism is probably that cationic particles have electrostatic interaction and mucosal adhesion with negatively charged membrane of the contacted organs, such as skin, 27,28 eyes, 26,29 and gastrointestinal mucosa, 30,31 to improve drugs' retention and permeability. 26,30 Chitosan is a kind of cationic alkaline polysaccharide extracted from crustaceans and is widely used in biomedical engineering with good biocompatibility and biodegradability.…”
Section: Liu Et Almentioning
confidence: 99%
“…Many efforts in ophthalmic drug delivery have been devoted to elongate the contact time of the vehicle at ocular surface, slow down the elimination of the drug, to improved patient compliance, to increase bioavailability and increase its corneal penetration 48 .Studies have shown that NEs have the ability to provide sustained release of a drug and higher penetration to the deeper layers of the ocular structure and aqueous humor and hence as compared to conventional system of the drug delivery NE enhances the therapeutic efficacy and pharmacokinetic parameters of the drug 47,49 .…”
Section: Ocular Deliverymentioning
confidence: 99%